A=\(x^2-4x+5\)
Ta có : A=\(x^2-4x+4+1=\left(x^2-2x2+2x^2\right)+1\)
=> A= \(\left(x-2\right)^2+1\)
Vì \(\left(x-2\right)^2\) > hoặc = 0 với mọi \(x\)
=> \(\left(x-2\right)^2+1\) > hoặc = 1 với mọi \(x\)
=> A > hoặc = 1 với mọi \(x\)
Do đó GTNN của A =1 đạt được khi \(\left(x-2\right)^2=0\)
\(x-2=0\)
\(x=2\)
Vậy min của A=1 tại x=2
\(A=x^2-4x+5\)
\(A=x^2-2.x.2+4+1\)
\(A=\left(x-2\right)^2+1\)
Vì \(\left(x-2\right)^2\ge0\) với mọi x
\(\Rightarrow\left(x-2\right)^2+1\ge1\) với mọi x
\(\Rightarrow Amin=1\Leftrightarrow x=2\)
\(B=2x^2+4x+5\)
\(B=2\left(x^2+2x+\dfrac{5}{2}\right)\)
\(B=2\left(x^2+2x+1-1+\dfrac{5}{2}\right)\)
\(B=2\left(x+1\right)^2+3\)
Vì \(2\left(x+1\right)^2\ge0\) với mọi x
\(\Rightarrow2\left(x+1\right)^2+3\ge3\) với mọi x
\(\Rightarrow Bmin=3\Leftrightarrow x=-1\)